(untitled) (Research, Society and Development, 2022)
Among the topics related to labor issues, hiring and the rights of professionals working on maritime cruises are a fruitful subject to be addressed in the field of debate. The study aimed to analyze these issues, focusing on the problem of crew location. Sometimes in national waters, sometimes in foreign waters, these workers live not only with their work routine, but also with the doubt of which legislation applies to their profession: whether it is Brazilian law or international declarations and agreements. This is an exploratory and descriptive study of a qualitative nature. The study showed that despite advances in Brazilian legislation, it is still not possible to say precisely which law prevails, and in this context not only this complex situation but also rights such as overtime and night shift that are guaranteed by national legislation are vilified by foreign companies. of cruises. Faced with such a scenario, the study concludes that it is necessary to deepen the discussions on this issue, since those who are working there are human beings in search of a dignified life, which needs to be preserved and with labor rights duly protected.